Harum manis plantation suitability analysis in Perlis by using analytic hierarchy process method / Nur Aina Fitriah Noor Azman - Noor Azman, Nur Aina Fitriah (2024)
Plantation suitability analysis is component of effective land to optimize land and ensure sustainable agricultural practices. The study area decided to be in Perlis, Malaysia. The aim of this study is to apply AHP method in GIS to assess land suitability for Harum Manis plantation. To achieve the aim, the objectives of this study are to assign weight and rank of each influencing factor by using pair-wise matrix in AHP method and to produce suitability Harum Manis Plantation. Data collection that will conduct by a systematic approach involving criteria identification, pairwise comparisons and AHP-based analysis. Spatial data integrate to soil quality, rainfall, land use, elevation and slope are integrated using Geographic Information Systems (GIS) to create a plantation suitability map. The findings are producing Harum Manis Plantation map that shown the highly suitable 22%, moderately suitable 55%, marginally suitable 20% and not suitable 3% that overlay of factors’ percentage. For recommendation that is further research make improve that have many factors for updating the data for relevant.